Comunicación del conocimiento propio y relaciones discursivas en el género tesis - Paulina Meza; Iria da Cunha (Sintagma, 2019)
One of the greatest challenges for a college student, from any academic degree, is writing a thesis. In doing so, candidates must deal with the difficulties of expressing their own knowledge, for example, elaborating a research justification. In this work, our hypothesis is that there exist some functions in communicating one’s knowledge (FCCPs) in the thesis genre that have a significant correspondence with the discourse relations (DRs) of the rhetorical structure theory (RST). This correlation would provide students with the discourse marks frequently used in the expression of FCCPs in such genre and, thus, help them to write their thesis properly. In this context, the purpose of this study is to determine the point of significant correspondence between FCCPs and DRs in the thesis genre. Based on the correlation between FCCPs and DRs, we have proposed two complementary strategies to help students express their own knowledge in their thesis.